(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In a pesticide free pear-orchard, in Koropi, Attica (Greece) during the year 1994-1996 it was found a satisfactory number ofpredacious insects belonging to the farnilies Chrysopidae and Anthocoridae; the most representatives were Chrysoperla carnea Steph. and Anthocoris nemoralis F. The role of C. carnea and A. nemoralis is proven and justifiably so, both are considered to be the most active in the control of pear psylla populations ( Cacopsylla pyri L.). Additionally in the same pear orchard were found many predacious Coccinellidae while their activity does not appear to play an important role in the control of the psylla population since their presence in the field is rather incidental. In the field C. carnea appears first in February or March and A. nemoralis follows in March. The population of these insects increases gradually following the population increases of their host. The highest density is observed from the end of April till the end of July. Reduction of their population follows during the summer months to reach again satisfactory levels in the end of September. Especially A. nemoralis will survive in nature until the end of November and its population will disappear contemporary with the psylla population.